Speech recognition in children with unilateral and bilateral cochlear implants in quiet and in noise - Dawood, Gouwa (Stellenbosch : Stellenbosch University, 2008)
Thesis (MAud (Interdisciplinary Health Sciences. Speech-Language and Hearing Therapy)--Stellenbosch University, 2008.